Dermal Versus Total Uptake of Benzene from Mineral Spirits Solvent During Parts Washing. Issue 7 (3rd February 2014) - Bogen, Kenneth T.; Sheehan, Patrick J.
<x xml:space="preserve">Abstract</x> Quantitative approaches to assessing exposure to, and associated risk from, benzene in mineral spirits solvent (MSS), used widely in parts washing and degreasing operations, have focused primarily on the respiratory pathway. The dermal contribution to total benzene uptake from such operations remains uncertain because measuring in vivo experimental dermal uptake of this volatile human carcinogen is difficult. Unprotected dermal uptake involves simultaneous sustained immersion events and transient splash/wipe events, each yielding residues subject to evaporation as well as dermal uptake. A two‐process dermal exposure framework to assess dermal uptake to normal and damaged skin was applied to estimate potential daily dermal benzene dose (Dskin) to workers who used historical or current formulations of recycled MSS in manual parts washers. Measures of evaporation and absorption of MSS dermally applied to human subjects were modeled to estimate in vivo dermal uptake of benzene in MSS. Uncertainty and interindividual variability in Dskin was characterized by Monte Carlo simulation, conditioned on uncertainty and/or variability estimated for each model input. Dermal exposures are estimated to average 33% of total (inhalation + dermal) benzene parts washing dose, with approximately equal predicted portions of dermal dose due to splash/wipe and to continuous contact with MSS. The estimated median (95th percentile) dermal and total daily benzene doses from parts washing are: 0.0069 (0.024) and 0.025 (0.18) mg/day using current, and 0.027 (0.085) and 0.098 (0.69) mg/day using historical, MSS solvents, respectively.